2003
DOI: 10.1084/jem.20021683
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy of Cytotoxic T Cell–resistant Tumors by T Helper 2 Cells

Abstract: Currently most attempts at cancer immunotherapy involve the generation of CD8+ cytotoxic T lymphocytes (CTLs) against tumor-associated antigens. Many tumors, however, have been immunoselected to evade recognition by CTLs and thus alternative approaches to cancer immunotherapy are urgently needed. Here we demonstrate that CD4+ T cells that recognize a secreted tumor-specific antigen and exhibit a cytokine secretion profile characteristic of Th2 cells, are capable of clearing established lung and visceral metast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
212
3
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 210 publications
(224 citation statements)
references
References 26 publications
8
212
3
1
Order By: Relevance
“…As discussed above, we did not observe any influence of STAT6 signaling on the differentiation of DCT-specific CD4 1 T cells, suggesting that STAT6 is also required downstream of the effector CD4 1 T cells. Consistent with our observation, Mattes et al [10] demonstrated that tumor regression mediated by transferred Th2 effector cells was dependent on the host expression of STAT6. Furthermore, there is ample evidence that STAT6 plays a critical role in the late phase of allergic asthma, in addition to its requirement in Th2 differentiation [32,33].…”
Section: Wt Vssupporting
confidence: 93%
See 3 more Smart Citations
“…As discussed above, we did not observe any influence of STAT6 signaling on the differentiation of DCT-specific CD4 1 T cells, suggesting that STAT6 is also required downstream of the effector CD4 1 T cells. Consistent with our observation, Mattes et al [10] demonstrated that tumor regression mediated by transferred Th2 effector cells was dependent on the host expression of STAT6. Furthermore, there is ample evidence that STAT6 plays a critical role in the late phase of allergic asthma, in addition to its requirement in Th2 differentiation [32,33].…”
Section: Wt Vssupporting
confidence: 93%
“…More importantly, this anti-tumor mechanism did not evoke fulminant autoimmune pathology. The utility of Th2 cells or IL-4 as anti-tumor effectors has been reported by others, and in some cases Th2 cells were more effective than Th1 cells in the clearance of cytotoxic T lymphocyte-resistant tumors [10]. Furthermore, a human clinical trial of Canvaxin, a cell-based vaccine, found that the magnitude of vaccine-induced Th2 immunity correlated with overall survival, and anti-tumor Th2 cells can be identified in cancer patients supporting the possibility of generating such populations in humans [30,31].…”
Section: Wt Vsmentioning
confidence: 61%
See 2 more Smart Citations
“…Even though the beneficial effect of TATE remains controversial, the presence of eosinophils appears as an indicator of good prognosis indicator in some cancers, such as head and neck cancers (7)(8)(9) and gastrointestinal cancers (10), particularly in colorectal cancers, in which high eosinophil counts were associated to increased 5-y survival (11). Clinical observations that eosinophil accumulation in intestinal tumors was associated to a better prognosis have been recently supported by experimental data in murine models (12)(13)(14).…”
mentioning
confidence: 60%